2015
DOI: 10.17344/acsi.2015.1358
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-based Colorimetric and Chemiluminescence Detection of Aflatoxin B1 in Foods Samples

Abstract: We developed a new biosensor for the detection of aflatoxin B1(AFB1) based on the interaction of gold nanoparticles (AuNPs) with the aptamer. Aggregation of AuNPs was induced by desorption of the AFB1 binding aptamer from the surface of AuNPs as a result of the aptamer target interaction leading to the color change of AuNPs from red to purple. The linear range of the colorimetric aptasensor covered a large variation of AFB1 concentrations from 80 to 270 nM and the detection limit of 7 nM was obtained. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 30 publications
(32 reference statements)
0
20
0
1
Order By: Relevance
“…The aptasensor is a particular class of biosensor and can be a good alternative to immunosensors because it is easier to synthesize and modify with a variety of chemical groups [67,68]. The difference of this sensor is in the biological recognition element, which is an aptamer instead of an antibody.…”
Section: Determinationmentioning
confidence: 99%
“…The aptasensor is a particular class of biosensor and can be a good alternative to immunosensors because it is easier to synthesize and modify with a variety of chemical groups [67,68]. The difference of this sensor is in the biological recognition element, which is an aptamer instead of an antibody.…”
Section: Determinationmentioning
confidence: 99%
“…Subsequently, stable gold aggregates are formed under the action of electrolytes or cationic polymers leading to the solution color changing. According to this aptasensing strategy, label-free AuNPs-based aptasensors were frequently reported for the rapid detection of mycotoxins [49], including ochratoxin A [38,40,50], aflatoxin B1 [27,51], and zearalenone [52]. Interestingly, Liu and collaborators have found that aromatic targets sch as ochratoxin A can also adsorb on the surface of AuNPs after aptamer folding and further inhibit salt-induced aggregation [40].…”
Section: Solution-based Assaysmentioning
confidence: 99%
“…Aptasensors for the detection of aflatoxin B 1 and M 1 exist in combination with a plethora of techniques: qPCR (Guo et al, 2014 ), split aptazymes (Seok et al, 2015 ), and dipstick assays (a more detailed description about the workflow for these easy to use sensors can be found in Section Drugs of Abuse Detection; Shim et al, 2014 ) as well as the more widely spread electrochemical (Nguyen et al, 2013 ; Istamboulié et al, 2016 ) and colorimetric (Malhotra et al, 2014 ), fluorescent (Wang B. et al, 2015 ) and chemiluminescent (Hosseini et al, 2015 ) gold nanoparticle based sensors. Some sensors were shown to work in spiked or real samples (Guo et al, 2014 ; Seok et al, 2015 ; Istamboulié et al, 2016 ) and with results similar to those obtained with the normally used immunoassays (Shim et al, 2014 ).…”
Section: Small Molecule Aptasensorsmentioning
confidence: 99%